ADOLESCENT PERCEPTIONS ABOUT EARLY MARRIAGE (Descriptive Study in SMAN 7 Sarolangun) - Vivi Dahlia; Netrawati Netrawati (Universitas Negeri Padang, 2019)
This research is motivated by the phenomenon of early marriage that occurs among adolescents. Early marriage is a marriage that starts from the age of 16 years to 19 years. The ideal age for getting married at the age of 21 years. This study aims to (1) describe adolescent perceptions about early marriage from the cognitive aspect (2) describe adolescent perceptions about early marriage viewed from the affective aspect (3) describe adolescent views about early marriage viewed from the conative aspect.The type of research used is quantitative with descriptive research. The sample in this study students of class X, XI, XII SMA 7 Sarolangun with 246 students. The data collection tool used was a questionnaire. Data analysis techniques using percentage techniques.The results showed that: The results showed that: (1) adolescents' perceptions of early marriage viewed from the cognitive aspects in Sarolangun 7 High School were in a fairly good category with a percentage of 80%, (2) adolescent perceptions about early marriage viewed from the affective aspects in Sarolangun 7 High School in the pretty good category with a percentage of 76%, (3) adolescent perceptions about early marriage seen from the cognitive aspects at SMA Negeri 7 Sarolangun are in the quite good category with a percentage of 56%. According to the research findings, counselor and teachers need to provide guidance and counseling services to adolescents regarding early marriage.